ANALISIS KINERJA KARYAWAN STUDI KASUS PT. REYCOM DOKUMEN SOLUSI - Mujibul Hakim (Jurnal Dinamika Ekonomi & Bisnis, 2019)
This study aims to describe the performance of employees who are at PT. Reycom Document Solutions, employee performance is still relatively low supported by research results. This research is a qualitative descriptive study, the subjects of this study are employees of PT. Reycom Document Solutions. Data collection is done by observation, interview and survey techniques. The validity of the data is done by triangulation of techniques and sources. Data analysis techniques using qualitative descriptive analysis techniques. The results of this study show good performance because it is influenced by several factors. The influencing factors are external factors, compensation and motivation for employee performance. Managerial implications of this research are HR Placement, work discipline, production targets, job satisfaction, motivation, compensation, management systems, bonuses / incentives, health benefits, family benefits, pensions, transportation and office facilities that have not been able to improve employee performance. Managerial should conduct an evaluation to improve employee performance at PT. Reycom Document Solutions.